Modal-semantic shades expressed by interrogative statements (Eurasian Journal of Philology Science and Education, 2023)
The article considers the modal-semantic shades expressed by interrogative statements in the Kazakh language, which are used to obtain not only certain information, but also to express approval (consent), clarification, advice, indication, suggestion, comparison, attention (to cause a reaction), conclusion, justification, warning, permission, prohibition, refusal, objection, protest, coercion (concession), request, entreaty, intimidation, accusation (acceleration). These modal-semantic meanings are expressed mainly in interrogative utterances by an interrogative pronoun, interrogative particles ма/ме, ша/шe, a concretizing particle ғой, linguistic units with an interrogative meaning (interjections), established structures and other stable phrases, the general content of the utterance, interrogative intonation. Also, these modal-semantic shades can be expressed in speech using an interrogative pronoun, an interrogative particle together with other various structures. The indicated modal-semantic meanings are enhanced by repeating the interrogative pronoun, the interrogative particle, words directly related to the requested information, and the use of other linguistic units (verb mood forms, analytical formants, etc.). When expressing the above modal meanings in the interrogative utterances, the content of the speech act with the interrogative meaning plays an important function, i.e. the holistic context (syntactic integrity), the pragmatic purpose of the speaker (author, hero), depending on the speech situation.Keywords:interrogative utterance, modal semantic shades, interrogative pronoun, interrogative particle.